Folate, Vitamin B12 and Serum Ferritin Levels by Age and Gender in Children Presenting with Protein and Energy Insufficiency: A Retrospective Review - Veysel Tahiroğlu; Erkam Coşkun; Erhan Sönmez; Naci Ömer Alayunt (Çocuk Dergisi)
Objectives: The aim of this study is to determine the levels of folate, vitamin B12, and ferritin according to gender and age groups in children who visited the hospital with the complaint of protein and energy deficiency. Methods: Folate levels of 74 patients with protein and energy deficiency complaints, vitamin B12 levels of 184 patients, and ferritin levels of 187 people who were admitted to the hospital were included in the study. The hospital reference ranges for children were used to diagnose folate, vitamin B12, and ferritin levels and to determine their normal ranges. Results: When the folate levels were examined in the study, it was determined that approximately 2% of the children in the 0-6 age group were below <3.89 ng/mL, and all of the children in the 7-18 age group were within the normal range. When the vitamin B12 levels are examined, it was determined that 3.3% of the children had a vitamin B12 level below 191 ng/L, and 14.3% of the 7-18 age group were below 191 ng/L. Considering the ferritin levels, it was determined that 51.6% of the children were below 30 µg/L. When evaluated according to gender, the majority of folate and B12 levels in both men and women were within the normal range, while 47.1% of women and 41% of men had ferritin levels below the normal range. Conclusion: It was observed that the folate, vitamin B12, and ferritin levels of the patients could vary according to geographical regions. For this reason, we think that it should be focused on the 0-6 age range, where the incidence of micronutrient deficiencies and infectious diseases is the highest.